Functional Annotation of All Salmonid Genomes (Faasg): An International Initiative Supporting Future Salmonid Research, Conservation and Aquaculture - Vidal-Soto, R (BioMed Central Ltd., 2017)
We describe an emerging initiative - the Functional Annotation of All Salmonid Genomes (FAASG), which will leverage the extensive trait diversity that has evolved since a whole genome duplication event in the salmonid ancestor, to develop an integrative understanding of the functional genomic basis of phenotypic variation. The outcomes of FAASG will have diverse applications, ranging from improved understanding of genome evolution, to improving the efficiency and sustainability of aquaculture production, supporting the future of fundamental and applied research in an iconic fish lineage of major societal importance. © 2017 The Author(s).